2014
DOI: 10.1371/journal.pone.0104574
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Genetic Variation in FTO rs9939609 on Obesity and Dietary Preferences in Chinese Han Children and Adolescents

Abstract: The association of the rs9939609 single nucleotide polymorphism in FTO gene with obesity has been extensively investigated in studies of populations of European, African, and Asian ancestry. However, inconsistent results have been reported in Asian populations, and the relationship of FTO variation and dietary behaviors has only rarely been examined in Chinese children and adolescents. The aim of this study was to assess the association of rs9939609 with obesity and dietary preferences in childhood in a Chines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 67 publications
2
21
0
5
Order By: Relevance
“…Similar results have been reported for the FTO polymorphism, which has been shown to be associated with anthropometric and biochemical variables, as well as with excess body weight (Dina et al, ; Frayling et al, ; Gerken et al, ; Liu et al, ; Reuter et al, ; Yang et al, ). For example, allele A of the rs9939609 polymorphism of the FTO gene was associated with greater accumulation of body fat, an increase in BMI, waist and hip circumference, blood pressure, triglycerides and low‐density lipoprotein cholesterol, and a further decrease in high‐density lipoprotein cholesterol (Dina et al, ; Frayling et al, ; Gerken et al, ; Liu et al, ; Reuter et al, ; Solak et al, ; Yang et al, ). However, other studies found no association between the FTO polymorphism and weight status (Fawwad et al, ; Solak et al, ), which is in agreement with the results of our study.…”
Section: Discussionsupporting
confidence: 77%
“…Similar results have been reported for the FTO polymorphism, which has been shown to be associated with anthropometric and biochemical variables, as well as with excess body weight (Dina et al, ; Frayling et al, ; Gerken et al, ; Liu et al, ; Reuter et al, ; Yang et al, ). For example, allele A of the rs9939609 polymorphism of the FTO gene was associated with greater accumulation of body fat, an increase in BMI, waist and hip circumference, blood pressure, triglycerides and low‐density lipoprotein cholesterol, and a further decrease in high‐density lipoprotein cholesterol (Dina et al, ; Frayling et al, ; Gerken et al, ; Liu et al, ; Reuter et al, ; Solak et al, ; Yang et al, ). However, other studies found no association between the FTO polymorphism and weight status (Fawwad et al, ; Solak et al, ), which is in agreement with the results of our study.…”
Section: Discussionsupporting
confidence: 77%
“…In line with evidence in adults, studies have shown that FTO rs9939609 genotype was associated with childhood obesity [59,60,61,62], and also suggested an association of the FTO variant and dietary intake and preference [59,61,63]. We previously reported results of a combined analysis of 16,094 boys and girls from 14 studies [63], and found that BMI-increasing allele of the FTO variant was associated with increased total energy intake, but not with protein, carbohydrate, or fat intake.…”
Section: Dietary and Lifestyle Factors Interact With Genetic Variasupporting
confidence: 63%
“…Test-retest reliability was assessed by re-administering the questionnaire 4 weeks later, and validity was assessed by comparing 3-day food records. The reliability (Cronbach's α) and content validity of the questionnaire were 0.86 and 0.88, respectively (Yang et al, 2014).…”
Section: Anthropometric Measurements and Epidemiologic Investigationmentioning
confidence: 96%
“…The genetic risk score (GRS), which was calculated with the sum of risk alleles of the five SNPs of rs17782313, rs543874, rs2241423, rs11084753 and FTO rs9939609 which was the research results of our laboratory published earlier (Yang et al, 2014), was used to evaluate the cumulative effect of the risk SNPs. The GRS was positively correlated with the risks of obesity after being adjusted for age and sex (P trend = 8.50 × 10 − 15) (Fig.…”
Section: Cumulative Effect Of the Snps On Obesity Riskmentioning
confidence: 99%